Effects of geomagnetic storm on low latitude ionospheric total electron content: A case study from Indian sector - Chakraborty, Monti (2015)
The effect of geomagnetic storms on low latitude ionosphere has been investigated with the help of Global Positioning System Total Electron Content (GPS-TEC) data. The investigation has been done with the aid of TEC data from the Indian equatorial region, Port Blair (PBR) and equatorial ionization anomaly region, Agartala (AGR). During the geomagnetic storms on 24th April and 15th July 2012, significant enhancement up to 150% and depression up to 72% in VTEC is observed in comparison to the normal day variation. The variations in VTEC observed from equatorial to EIA latitudes during the storm period have been explained with the help of electro-dynamic effects (prompt penetration electric field (PPEF) and disturbance dynamo electric field (DDEF)) as well as mechanical effects (storm-induced equatorward neutral wind effect and thermospheric composition changes). The current study points to the fact that the electro-dynamic effect of geomagnetic storms around EIA region is more effective than at the lower latitude region. Drastic difference has been observed over equatorial region (positive storm impact) and EIA region (negative storm impact) around same longitude sector, during storm period on 24th April. This drastic change as observed in GPS-TEC on 24th April has been further confirmed by using the O/N2 ratio data from GUVI (Global Ultraviolet Imager) as well as VTEC map constructed from IGS data. The results presented in the paper are important for the application of satellite-based communication and navigational system.